Outcome of Neonatal Acute Kidney Injury in a Special Care Baby Unit (SCABU) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Acute kidney injury (AKI) is common in neonates admitted in Special Care Baby Unit (SCABU) with high morbidity and mortality.Objective: The present study was intended to see the immediate hospital outcome of neonatal acute kidney injury (AKI) in a Special Care Baby Unit (SCABU).Methods: This observational study was carried out in SCABU, in the Department of Paediatrics, Dhaka Medical College Hospital, from October 2013 to March 2014. A total of 44 neonates (from 3-28 days) with AKI were included in this study. AKI staging was done by using pediatric RIFLE criteria as Risk, Injury, Failure. Patients were managed conservatively and immediate hospital outcome was assessed by SCABU stay, multiorgan failure, resolution of AKI, mortality and dialysis as needed.Results: Demographic profile among the study population the neonate of d”7 days old comprised the main bulk. Majority of the neonates were of average birth weight. The diagnosis was based on estimated creatinine clearance(eCCL) criteria of pRIFLE showed that 40.9% neonates were at risk of AKI, 20.5% have had already injured. Higher proportions of neonates were classified as failure (38.6%).Outcome variables of neonatal AKI predicted by pRIFLE criteria was significantly higher in failure group in respect to SCABU stay (12.1+ 7.9) p value < 0.001, multiorgan failure (41.2 %) p value 0.026 and dialysis needed (88.2 %) p value < 0.001, resolution from AKI (47.1%) p value 0.885, Mortality (41.2%) p value 0.106. Here 43% neonates with AKI were improved with normal renal function and 29% improved with impaired renal function. Increased frequency of death (28%) in this series was due to multiorgan involvement and significantly higher in failure group with adequate dialysis support.Conclusion: From the findings of the study it can be concluded that immediate hospital outcome of neonatal AKI is worst even after adequate dialysis support. Multiorgan involvements, increase length of hospital stay at SCABU, increase need for dialysis, are the important cause of increase mortality and morbidity. So, early detection, prompt referral and immediate supportive therapy could improve the outcome of neonatal AKI.DS (Child) H J 2018; 34(1) : 5-10